ANALYSIS OF HEMODIALYSIS PERIODS, AGE, AND SMOKING TOWARDS THE SEVERITY OF ERECTILE DYSFUNCTION IN PATIENTS WITH CHRONIC RENAL FAILURE ON ROUTINE HEMODIALYSIS - Saga Aditya Hutama; Besut Daryanto; Medianto; Atma Gunawan (Jurnal Urologi Indonesia, 2023)
Objective: This study aims to analyze the factors associated such as hemodialysis periods, age, and smoking with ED severity in CKD patients undergoing routine hemodialysis. Material & Methods: A single-center, cross-sectional study was conducted involving a total 101 patients who were on routine hemodialysis who diagnosed with CKD and experienced complaint in sexual function were included. The severity of ED classified based on the International Index of Erectile Function (IIEF-5). The analysis was carried out descriptively and analytically using the ordinal regression method. Results: Hemodialysis duration (p = 0.044) were significantly related to severity of erectile dysfunction in patient with CKD and on routine hemodialysis. Meanwhile, although both older age (p =0.307) and smoking (p = 0.283) showed a positive estimate, they were not statistically significant. Conclusion: The study indicate that prevalence of ED observed in CKD patient with routine hemodialysis remain high. Several factors significantly contribute in ED severity such as shorter hemodialysis duration.